Pengaruh Subtitusi Monosium Glutamat dengan Bubuk Kaldu Produk Hasil Samping Pembekuan Udang terhadap Karakteristik Stik Keju - Ramli Ramli; Ismi Jasila; Sawiya Sawiya (Jambura Fish Processing Journal, 2026)
Monosodium glutamate (MSG) is often added as a flavor enhancer during the production of cheese sticks, because without MSG, the flavor is less savory or less appealing and tends to be less popular with consumers. The use of high levels of MSG to impart umami (savory) flavor can have adverse health effects. Therefore, there is a need for alternative food additives to replace MSG that possess characteristics similar to MSG—namely, acting as flavor enhancers—but do not have negative health effects or, if possible, may even have positive health effects. A food additive that can be selected as an alternative to MSG is broth powder derived from shrimp freezing byproducts. The objective of this study was to determine the effect of substituting monosodium glutamate with broth powder derived from shrimp freezing byproducts on the characteristics of cheese sticks. This study was conducted using a laboratory experimental method with a quantitative approach, employing a Completely Randomized Design (CRD). The results showed that substituting monosodium glutamate with shrimp freezing by-product broth powder had a significant effect on color, aroma, taste, and brittleness, but no significant effect on texture. The best treatment was Treatment P1, which consisted of 75% MSG and 25% shrimp broth powder.